Ab Initio Study of Proton Transfer and Hydration in Phosphorylated Nata de Coco - Sitti Rahmawati; Cynthia Linaya Radiman; Muhamad Abdulkadir Martoprawiro (Indonesian Journal of Chemistry, 2017)
This research aims to calculate energetics parameters, hydrogen bonding, characteristics local hydration, and proton transfer in phosphorylated nata de coco (NDCF) membrane using ab initio method. The minimum energy structure of NDCF membranes and the addition of n water molecules (n = 1-10) determined at the B3LYP/6-311G** level indicates that proton dissociation requires a minimum of four water molecules. Dissociated protons stabilize with the formation of (hydronium, Zundel, Eigen) ions. Calculation of the interaction energy with n water molecules indicates an increasingly negative change in energy (ΔE) and enthalpy (ΔH), and hence an increasingly positive interaction with water molecules. This interaction facilitates the transfer of protons in the membrane matrix. Calculation of the rotational energy at the center of C-O indicates that the pyranose ring structure, with a maximum barrier energies of ~ 12.5 J/mol, is much more flexible than the aromatic backbones of sulfonated poly(phenylene) sulfone (sPSO2) and the polytetrafluoroethylene (PTFE) backbones in perfluorosulfonic acid ionomers (PFSA). These energy calculations provide the basis that the flexibility of the pyranose ring and the hydrogen bonding between water molecules and phosphonate groups influence the transfer of protons in the membrane of NDCF.